On the role of TFEC in reptilian coloration - Tzika, Athanasia C. (Frontiers in Cell and Developmental Biology, 2024)
Reptilian species, particularly snakes and lizards, are emerging models of animal coloration. Here, I focus on the role of the TFEC transcription factor in snake and lizard coloration based on a study on wild-type and piebald ball pythons. Genomic mapping previously identified a TFEC mutation linked to the piebald ball python phenotype. The association of TFEC with skin coloration was further supported by gene-editing experiments in the brown anole lizard. However, novel histological analyses presented here reveal discrepancies between the ball python and anole TFEC mutants, cautioning against broad generalizations. Indeed, both wild-type and piebald ball pythons completely lack iridophores, whereas the TFEC anole lizard mutants lose their iridophores compared to the wild-type anole. Based on these findings, I discuss the potential role of the MiT/TFE family in skin pigmentation across vertebrate lineages and advocate the need for developmental analyses and gene-editing experiments to explore the reptilian coloration diversity.